Weighting of constitutional rights: principles and values in Colombia - Cabrera Suárez, Lizandro Alfonso (DIXI, 2020)
Subject and scope: The techniques for the weighting of rights, which the Colombian Constitutional Court has adopted in a singular way over the last twenty years of its existence, have made it possible to find a reasonable solution to numerous clashes between fundamental rights and have turned this judicial corporation into a model of world interpretation. Characteristics: These techniques have a specific philosophical and historical root that must be envisioned. Findings: Legal science, for due reflection and updating, in the face of new dynamics and collision between rights, must incorporate the weighting of constitutional rights. Conclusions: The principles are in the legal life of Colombia; they are the support of the Social State of Law.